A validated UHPLC–MS/MS method for the measurement of riluzole in plasma and myocardial tissue samples. (10th July 2017) - Parker, Suzanne L.; Guerra Valero, Yarmarly C.; Lipman, Jeffrey; Weiss, Steven; Smith, Camilla; Russell, Lyndal; Smith, Paul; Roberts, Jason A.; Wallis, Steven C.
Abstract: Through blocking the cardiac persistent sodium current, riluzole has the potential to prevent myocardial damage post cardiac bypass surgery. A sensitive UHPLC–MS/MS method was developed and validated for quantitation of riluzole and 5‐methoxypsoralen in human plasma and myocardial tissue homogenate using a liquid–liquid extraction with dichloromethane. The chromatographic separation was achieved using Shimadzu Shim‐pack XR‐ODS III, 2.0 × 50 mm, 1.6 μm column with a gradient mobile phase comprising methanol and ammonium acetate buffer pH 3.6 in purified water. The analyte and internal standard were separated within 3.5 min. Riluzole quantitation was achieved using the mass transitions of 235–138 for riluzole and 217–156 for 5‐methoxypsoralen. The method was linear for riluzole plasma concentrations from 0.2 to 500 ng/mL and myocardial tissue homogenate concentrations from 0.2 to 100 ng/mL. The method developed was successfully applied to a clinical study for patients receiving riluzole while undergoing cardiac bypass surgery.